(untitled) (Jurnal Bina Praja, 2016)
Nowadays, traditional market is increasingly squeezed by the emergence of modern market that develops rapidly. The dominance shift in national retail is apparent when globalization can no longer be contained, let alone be banned. Middle class and small class (traditional market) business retail seem to be in increasingly difficult condition to compete with upscale retail business (modern market). The purpose of this study is to analyze the factors influencing the competitiveness of traditional market and to develop policies to improve the competitiveness of traditional market. This study utilizes research strategy of case study in Bandung City, Serang City, and Surabaya City with qualitative descriptive approach. The study shows that the factors inhibiting the competitiveness of traditional market with modern stores are (1) Traditional market’s bad image, and (2) Traditional market’s sellers and managers are unprofessional. To improve the competitiveness of traditional market, this study recommends: (1) routine and regular maintenance of buildings and infrastructure of traditional market, (2) professionalism improvement of traditional market’s sellers and managers, and (3) the partiality of local government in traditional markets.